2016
DOI: 10.5588/ijtld.15.0053
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis screening outcomes for newly diagnosed persons living with HIV, Nyanza Province, Kenya, 2009

Abstract: SUMMARY SETTING Fifteen human immunodeficiency virus (HIV) clinics in Nyanza Region, Western Kenya. OBJECTIVE To describe routine tuberculosis (TB) screening and diagnostic practices among newly enrolled people living with HIV (PLHIV) prior to the implementation of World Health Organization recommended TB intensified case finding. DESIGN Retrospective chart abstraction of PLHIV aged ⩾7 years who were newly enrolled in HIV care in July and August 2009, and who had not received antiretroviral treatment in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
3
6
0
1
Order By: Relevance
“…In another study in Kenya among 1,060 newly enrolled PLHIV, 62% reported symptoms of TB, but only 26 cases of TB were found. This demonstrates the higher prevalence of symptoms among PLHIV prior to attending HIV services and the low sensitivity of TB screening (12). Our finding is similar to other longitudinal repeated screening of cohorts of PLHIV (21).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In another study in Kenya among 1,060 newly enrolled PLHIV, 62% reported symptoms of TB, but only 26 cases of TB were found. This demonstrates the higher prevalence of symptoms among PLHIV prior to attending HIV services and the low sensitivity of TB screening (12). Our finding is similar to other longitudinal repeated screening of cohorts of PLHIV (21).…”
Section: Discussionsupporting
confidence: 87%
“…Ninety-five percent (95.67%) of the visitors recorded in the study cohort had TB screening. Routine TB screening is in line with the WHO recommendations (18), and such high TB screening scores among PLHIV has also been reported in other studies (12,(19)(20)(21). TB screening is known to be good to rule out TB disease in PLHIV with a negative predictive value of 97.7% (22).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…More patients with HIV had sputum samples collected compared to those without HIV (29 samples vs 6 samples), which is likely related to an appropriately heightened clinical suspicion for TB among people living with HIV. 4 , 12 , 13 , 18 However, we saw a trend of positive smear results occurring more commonly in HIV negative individuals (83% smear positive rate) compared to HIV positive individuals (48% smear positive rate), supporting the often paucibacillary nature of HIV-associated TB. 19 Importantly, there was no difference in time to diagnosis for individuals with negative AFB smears compared to those with positive AFB smears, highlighting the delays in laboratory testing, processing of smear positive samples, and diagnosis among co-infected persons.…”
Section: Discussionmentioning
confidence: 60%
“…It is possible that the use of more sensitive diagnostic tests may have resulted in a higher TB diagnostic rate. [ 14 ] The TB Score chart had the highest diagnostic yield in children since it is comprised of a number of signs and symptoms and laboratory and radiological investigations which may have improved its yield. Sputum microscopy had the lowest diagnostic yield (20%) due to difficulties in expectoration of quality sputum in children and children most often have paucibacillary disease.…”
Section: Discussionmentioning
confidence: 99%